Condição muscular e deglutição na doença pulmonar obstrutiva crônica - Rockenbach, Nathalia de Morais (2021)
In addition to pulmonary involvement, chronic obstructive pulmonary disease (COPD) causes different systemic changes, among them muscle dysfunction. Such alteration can also have repercussions on swallowing since muscle activity during the transfer of the bolus from the mouth to the esophagus needs to be adequate in order to maintain airway protection. Thus, the objective of the present study was to analyze the relationship between handgrip strength (HGS) and pharyngeal transit time (FTT) in individuals with COPD. This was a quantitative, cross-sectional, and descriptive study through the analysis of secondary data of the individual database type. The sample was composed of 16 individuals diagnosed with COPD, of both genders and a mean age of 65.7 years. Information regarding FPM, FPM asymmetry, Videofluoroscopy of Swallowing (VFD), Volume-Viscosity Swallow Test (V-VST) protocol, and Body Mass Index (BMI) were collected from the medical charts. The data were statistically analyzed using the SPSS (Statistical Package for Social Sciences) statistical package, version 26.0. Pearson's correlation test, sample effect calculation, and binary logistic regression were performed. It was observed that most individuals presented severe COPD (62.5%), reduced FPM, and proportional BMI among the classifications (malnutrition, eutrophy, obesity). It was also found that most individuals had normal deglutition (43.75%), V-VST without changes (62.5%), and TTF for liquid of 0.88 seconds and for pasty of 0.81 seconds. As for the correlations between the variables, no significant correlation was observed between the swallowing classification and the rest of the variables. However, a significant correlation (p = 0.012), even if weak (r = -0.608), was obtained between TTF and non-dominant FPM (FPM-ND). In order to verify the presence of risk for swallowing, the dependent variable V-VST and the independent variables FPM-D, FPM-ND, and FPM asymmetry were considered for regression. However, the variables were not significant for the prediction model. This study showed that individuals with COPD have slower TTF and weak negative correlation only between the TTF and FPM-ND variables. Furthermore, it was not possible to consider FPM and FPM asymmetry as risk variables for swallowing changes.